Medical Mask Detection using advanced MobileNetV2 - Mandal, Gouranga; Bandaru, Lokesh; Jaka, Prasanth; Beeram, Nithin (The ... CSI International Symposium on Artificial Intelligence & Signal Processing (Online), 2023)
According to data from the World Health Organization (WHO), personal contact and respiratory droplets are the two main ways that the COVID-19 virus is spread. One of the prophylactic strategies that can stop the spread of COVID-19 and other respiratory viral illnesses is wearing a surgical mask. Therefore, it is essential to correctly wear a mark in public settings like supermarkets and shopping centers. In this study, we suggest a Face Mask Detection system to determine whether or not someone is correctly donning a mask. Face mask identification in video streams has only been the subject of a few studies. It uses OpenCV, TensorFlow-Keras, MobileNetV2, and Deep Learning to recognize face masks in a two-phase design and achieved an excellent accuracy.